Transforming growth factor-beta 1 produced by vascular smooth muscle cells predicts fibrosis in the gastrocnemius of patients with peripheral artery disease. Issue 1 (December 2016) - Ha, Duy; Carpenter, Lauren; Koutakis, Panagiotis; Swanson, Stanley; Zhu, Zhen; Hanna, Mina; DeSpiegelaere, Holly; Pipinos, Iraklis; Casale, George
Abstract Background Lower leg ischemia, myopathy, and limb dysfunction are distinguishing features of peripheral artery disease (PAD). The myopathy of PAD is characterized by myofiber degeneration in association with extracellular matrix expansion, and increased expression of transforming growth factor-beta 1 (TGF-β1; a pro-fibrotic cytokine). In this study, we evaluated cellular expression of TGF-β1 in gastrocnemius of control (CTRL) and PAD patients and its relationship to deposited collagen, fibroblast accumulation and limb hemodynamics. Methods Gastrocnemius biopsies were collected from PAD patients with claudication (PAD-II; N = 25) and tissue loss (PAD-IV; N = 20) and from CTRL patients (N = 20). TGF-β1 in slide-mounted specimens was labeled with fluorescent antibodies and analyzed by quantitative wide-field, fluorescence microscopy. We evaluated co-localization of TGF-β1 with vascular smooth muscle cells (SMC) (high molecular weight caldesmon), fibroblasts (TE-7 antigen), macrophages (CD163), T cells (CD3) and endothelial cells (CD31). Collagen was stained with Masson Trichrome and collagen density was determined by quantitative bright-field microscopy with multi-spectral imaging. Results Collagen density increased from CTRL to PAD-II to PAD-IV specimens (all differences p < 0.05) and was prominent around microvessels. TGF-β1 expression increased with advancing disease (all differences p < 0.05), correlated with collagen density across all specimens (r = 0.864; p < 0.001), associated with fibroblast accumulation, and was observed exclusively in SMC. TGF-β1 expression inversely correlated with ankle-brachial index across PAD patients (r = −0.698; p < 0.001). Conclusions Our findings support a progressive fibrosis in the gastrocnemius of PAD patients that is caused by elevated TGF-β1 production in the SMC of microvessels in response to tissue hypoxia.